Francesca Trivellato: The Familiarity of Strangers: The Sephardic Diaspora, Livorno, and Cross-Cultural Trade in the Early Modern Period. New Haven & London, Yale University Press, 2009, 470 págs. - Lamikiz Gorostiaga, Xabier (Investigaciones de Historia Económica, 2019)
Sin resumen